Middleware for providing activity-driven assistance in cyber-physical production systems. Issue 1 (26th December 2020) - Dhiman, Hitesh; Röcker, Carsten
Abstract: Assistance is becoming increasingly relevant in carrying out industrial work in the context of cyber-physical production systems (CPPSs) and Industry 4.0. While assistance in a single task via a single interaction modality has been explored previously, crossdevice interaction could improve the quality of assistance, especially given the concurrent and distributed nature of work in CPPSs. In this paper, we present the theoretical foundations and implementation of MiWSICx ( Mi ddleware for W ork S upport in I ndustrial C ontex ts ), a middleware that showcases how multiple interactive computing devices such as tablets, smartphones, augmented/virtual reality glasses, and wearables could be combined to provide crossdevice industrial assistance. Based on activity theory, MiWSICx models human work as activities combining multiple users, artifacts, and cyber-physical objects . MiWSICx is developed using the actor model for deployment on a variety of hardware alongside a CPPS to provide multiuser, crossdevice, multiactivity assistance. Graphical Abstract: